Squid impact analyser: uma ferramenta para análise de impacto de mudança em linhas de produto de software - Vianna, Alexandre Strapação Guedes (2012)
Software Products Lines (SPL) is a software engineering approach to developing software system families that share common features and differ in other features according to the requested software systems. The adoption of the SPL approach can promote several benefits such as cost reduction, product quality, productivity, and time to market. On the other hand, the SPL approach brings new challenges to the software evolution that must be considered. Recent research work has explored and proposed automated approaches based on code analysis and traceability techniques for change impact analysis in the context of SPL development. There are existing limitations concerning these approaches such as the customization of the analysis functionalities to address different strategies for change impact analysis, and the change impact analysis of fine-grained variability. This dissertation proposes a change impact analysis tool for SPL development, called Squid Impact Analyzer. The tool allows the implementation of change impact analysis based on information from variability modeling, mapping of variability to code assets, and existing dependency relationships between code assets. An assessment of the tool is conducted through an experiment that compare the change impact analysis results provided by the tool with real changes applied to several evolution releases from a SPL for media management in mobile devices